Antiviral Effect of Different Essential Oils on Avian Coronavirus - Okino, Cintia Hiromi; Melito, Gláucia Roberta; Astolfo, Maria Eduarda de Almeida; Martins, Maria Eduarda Da Mata [UNESP]; Junior, Stanislau Bogusz; Ferreira, Marcos David (American Association of Avian Pathologists (AAAP), 2024)
Plant essential oils (EOs) possess established antimicrobial properties; however, research on their antiviral activity, particularly against avian coronaviruses, remains limited. EOs offer a promising plant-based alternative for viral control, especially in scenarios where conventional chemical use is restricted. This study aimed to evaluate the antiviral effects of six different essential oils derived from Syzygium aromaticum, Origanum vulgare, Cymbopogon martinii, Cymbopogon citratus, Mentha piperita, and Mentha spicata against avian coronavirus (AvCov) at 0.1% and 1% dilutions. The antiviral effects of the EOs were assessed via virus isolation from embryonated chicken eggs, and the ability of the EOs to inhibit AvCoV replication was evaluated. The EOs from Syzygium aromaticum, Origanum vulgare, Cymbopogon martinii, and Cymbopogon citratus completely inhibited AvCov replication at a 1% dilution. Conversely, absent to partial inhibitory effect was observed at the 0.1% dilution for all tested EOs, with O. vulgare derived EO exhibiting the greatest inhibitory effect (over 70%). Notably, EOs from Mentha piperita and Mentha spicata were unable to completely inhibit AvCov at either concentration. Our findings highlight the potent antiviral activity of the EOs from Syzygium aromaticum, Origanum vulgare, Cymbopogon martinii, and Cymbopogon citratus against AvCov at a 1% dilution. The complete inhibition observed for these EOs suggests their potential for AvCov control. However, further research is necessary to elucidate the mechanisms of action, optimize formulations, and evaluate the efficacy against other coronaviruses, including those relevant to human health.

Nota de investigación- Efecto antiviral de diferentes aceites esenciales sobre el coronavirus aviar. Los aceites esenciales vegetales poseen propiedades antimicrobianas establecidas; sin embargo, la investigación sobre su actividad antiviral, particularmente contra los coronavirus aviares, sigue siendo limitada. Los aceites esenciales ofrecen una alternativa vegetal prometedora para el control viral, especialmente en escenarios donde el uso de químicos convencionales está restringido. Este estudio tuvo como objetivo evaluar los efectos antivirales de seis aceites esenciales diferentes derivados de Syzygium aromaticum, Origanum vulgare, Cymbopogon martinii, Cymbopogon citratus, Mentha piperita y Mentha spicata contra el coronavirus aviar (AvCov) en diluciones de 0.1% y 1%. Los efectos antivirales de los aceites esenciales se evaluaron mediante el aislamiento del virus a partir de huevos embrionados de pollo y se evaluó la capacidad de los aceites esenciales para inhibir la replicación del coronavirus aviar. Los aceites esenciales de Syzygium aromaticum, Origanum vulgare, Cymbopogon martinii y Cymbopogon citratus inhibieron completamente la replicación del coronavirus aviar en una dilución del 1%. Por el contrario, se observó un efecto inhibidor nulo o parcial con la dilución del 0.1% para todos los aceites esenciales analizados, siendo el aceite esencial derivado de O. vulgare el que exhibió el mayor efecto inhibidor (más del 70%). En particular, los aceites esenciales de Mentha piperita y Mentha spicata no pudieron inhibir completamente al coronavirus aviar en ninguna de las concentraciones. Nuestros hallazgos resaltan la potente actividad antiviral de los aceites esenciales de Syzygium aromaticum, Origanum vulgare, Cymbopogon martinii y Cymbopogon citratus contra coronavirus en una dilución del 1%. La inhibición completa observada para estos aceites esenciales sugiere su potencial para el control de coronavirus. Sin embargo, se necesitan más investigaciones para dilucidar los mecanismos de acción, optimizar las formulaciones y evaluar la eficacia contra otros coronavirus, incluidos los relevantes para la salud humana.
Keywords: antiviral; chicken; infectious bronchitis virus; RTqPCR; viral load